A real-world data study of the effect of co-solvent differences on the clinical safety of melphalan for injection - Wang, Guorong; Chen, Wenming; Zuo, Chenwei; Li, Huang; Yan, Jianzhou (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to compare the efficacy and safety of myeloablative conditioning with high-dose propylene glycol-free melphalan (PGF-Mel, EVOMELA®) versus propylene glycol melphalan (PG-Mel) in Chinese patients with multiple myeloma (MM) undergoing autologous stem cell transplantation (ASCT) in the real world.MethodsThis is a single-center, retrospective study of 107 patients with MM. Patients were divided into two groups based on their high-dose myeloablative conditioning regimen before autologous stem cell transplantation (ASCT): the EVOMELA® group (53 patients) and the PG-Mel group (54 patients). Qualitative data were compared using the two independent samples t-test and two independent samples Mann–Whitney U-test, and quantitative data were compared using the chi-square test. Efficacy and safety parameters were assessed and compared between the two groups.ResultsThe median time to myeloablation, the median time to platelet engraftment, and the neutrophil nadir were significantly lower in the EVOMELA® group than in the PG-Mel group (p < 0.05). In contrast, the median time to neutrophil engraftment, the lymphocyte nadir, and the number of platelet transfusions did not differ significantly between the two groups (p > 0.05). Adverse events, such as ionic disorders (hypokalemia, hypocalcemia, hypophosphatemia), nausea, diarrhea, vomiting, and loss of appetite, are significantly lower in the EVOMELA® group than in the PG-Mel group (p < 0.05), and the incidence of pyrexia between the two groups is not statistically different (p > 0.05). The average length of a hospitalization stay between the two groups was similar (p > 0.05). The EVOMELA® group had a higher CR rate (73.6% vs. 38.9%) and a lower PR rate (3.8% vs. 13.0%) than the PG-Mel group, indicating superior post-transplantation response outcomes for EVOMELA®. Median progression-free survival was 51.4 months (95% confidence interval (CI) 43.5–59.2) in the EVOMELA® group and 49.0 months (95% CI 39.7–58.3) (p = 0.115) in the PG-Mel group (HR 0.76, 95% CI 0.49–1.08; p = 0.116). Median overall survival was 56.2 months (95% CI 51.3–61.1) in the EVOMELA® group and 57.9 months (95% CI 53.5–62.4) (p = 0.007) in the PG-Mel group (HR 0.57, 95% CI 0.37–0.86; p = 0.008). The EVOMELA® group had a higher rate of minimal residual disease (MRD) negativity after ASCT (73.6% vs. 48.1%, p = 0.007) than the PG-Mel group.ConclusionEVOMELA® appears to demonstrate better efficacy and safety compared to PG-Mel; nonetheless, considering the study’s limitations, these observations warrant further rigorous investigation to confirm their validity.